GLACIERS OF THE KORYAK VOLCANO - T. M. Manevich; S. B. Samoilenko (Лëд и снег, 2015)
The paper presents main glaciological characteristics of present-day glaciers located on the Koryaksky volcano. The results of fieldwork (2008–2009) and high-resolution satellite image analysis let us to specify and complete information on modern glacial complex of Koryaksky volcano. Now there are seven glaciers with total area 8.36 km2. Three of them advance, two are in stationary state and one degrades. Moreover, the paper describes the new crater glacier.